Settlement of Default in the Coal Procurement Agreement Between PT. Semen Padang with PT. International Periodical Using Letter of Credit (L/C) - Aldyans Rio Pratra; Elwi Danil; Azmi Fendri (Dinasti Research, 2024)
In the Coal Sale and Purchase Agreement Number 39/PJJ/PBR.12/01.2008 between PT Semen Padang and PT Berkala International, payment is made by Domestic Documented Letter of Credit or Letter of Credit. For this reason, SKBDN Number MS 77106009548 was issued by PT Bank Mandiri in the amount of IDR 29,700,000,000.00,- to PT Berkala International. PT Berkala Internasional defaulted on not sending coal according to the agreed time. Using a case approach and normative juridical, primary data was obtained from PT. Semen Padang and secondary data are primary and secondary legal materials. To analyze the first problem, legal protection and contract theory are used, the second problem is dispute resolution theory. According to Article 1338 of the Civil Code, the consent made legally binding on the parties holding it, providing legal protection for PT Semen Padang to demand PT Berkala International, to do something, namely to deliver coal as stipulated in Article 1234 of the Civil Code. According to the contract theory, the agreement occurred after the party that received the offer, namely PT Berkala International, agreed to PT Semen Padang's offer to send coal. By filing a default lawsuit, the Padang District Court, the Padang High Court, and the Supreme Court, won PT Semen Padang.